POSTCOLONIAL ECOCRITICISM IN HUNGER BY ELISE BLACKWELL - Manggong, Lestari (Sanata Dharma University, 2020)
Hunger, a novella by a contemporary American novelist, Elise Blackwell, centres in the story of a Russian botanist, Nikolai Vavilov, during the Leningrad siege in 1941. Vavilov protects his collection of seeds at the Research Institute of Plant Industry in Leningrad against all odds, to be preserved for research for future use. In the recounting moments during the siege, the narrative provides parallelism between Leningrad and the ancient city of Babylon. In postcolonial writing, this can be perceived as a form of nostalgic projection of the past (Walder, 2011). Such a parallelism triggers a postcolonial narrative analysis on the pairing of the two as affinity, focusing on the significance of the comparison between the two cities (between the apocalyptic present and the glorious past). The contribution of this parallelism will be discussed to understand the novella as a narrative mode of ecocriticism, with regards to the idea of prioritizing seeds over human lives, which also acts as the steering issue stirring the plot. By mainly referring to Garrard (2004) and Huggan and Tiffin (2010) on ecocriticism and postcolonial ecocriticism, this essay in general aims to investigate how the novella contributes new perspectives on the intertwining between postcolonial studies and ecocriticism.